(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Automated blood cells extraction and counting in medical images is an important and sometimes necessary procedure in medical diagnostics and treatment. In this paper an automated blood cells extraction and counting method from microscopic images was proposed. The method is based on morphological filtering. The proposed method was tested using different background noises, resolutions and different colored images. The results are encouraging and the method gave an excellent performance for white blood cells and acceptable performance for red blood cells.